2001
DOI: 10.1007/bf03017355
|View full text |Cite
|
Sign up to set email alerts
|

Goal oriented general anesthesia for Cesarean section in a parturient with a large intracranial epidermoid cyst

Abstract: P Pu ur rp po os se e: : To illustrate the anesthetic management of a term parturient with a large brain tumour scheduled for Cesarean section.C Cl li in ni ic ca al l f fe ea at tu ur re es s: : A 26-yr-old woman presented at 33 weeks gestation with a generalized grand mal seizure. Magnetic resonance imaging demonstrated a 5-cm multi-lobulated extra axial mass compatible with an epidermoid cyst, arising from the left temporal lobe associated with shift of the midline structures and compression of the brainste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
(26 reference statements)
0
19
0
Order By: Relevance
“…The dose of remifentanil was derived from previous studies in both obstetric and non-obstetric patients, and was based on clinical safety and the ability to limit secondary effects. [7][8][9][10][11][12] In previous studies, both Ngan Kee and colleagues and Van de Velde and colleagues showed transient neonatal respiratory compromise lasting up to 5 min with remifentanil bolus in cesarean section under general anesthesia 7, 13 We also observed a significant reduction in Apgar scores in the remifentanil group at 1 and 5 min, with a concomitant difference in umbilical vein pH values, even though these remained in the normal range. These data indicate that, even at low doses, remifentanil has the potential to cause respiratory depression.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…The dose of remifentanil was derived from previous studies in both obstetric and non-obstetric patients, and was based on clinical safety and the ability to limit secondary effects. [7][8][9][10][11][12] In previous studies, both Ngan Kee and colleagues and Van de Velde and colleagues showed transient neonatal respiratory compromise lasting up to 5 min with remifentanil bolus in cesarean section under general anesthesia 7, 13 We also observed a significant reduction in Apgar scores in the remifentanil group at 1 and 5 min, with a concomitant difference in umbilical vein pH values, even though these remained in the normal range. These data indicate that, even at low doses, remifentanil has the potential to cause respiratory depression.…”
Section: Discussionmentioning
confidence: 45%
“…It provides hemodynamic stability in patients undergoing cesarean section under general anesthesia, 7 and has been successfully used in cases of maternal cardiac disease, 8,9 neurological conditions, preeclampsia and liver disease. [10][11][12] However, previous studies showed that the use of remifentanil to control the hemodynamic response to intubation and surgery is associated with transitory but significant neonatal depression. 7,13 Since this effect could be dose-dependent, 14 the aim of our study was to investigate whether administration of low-dose remifentanil could control the neuroendocrine response at cesarean section under general anesthesia without adverse effect on the neonate.…”
Section: Introductionmentioning
confidence: 95%
“…Numerous other regional analgesic techniques for post-caesarean section pain control have been reported in the literature. 5,6 The TAP block is a technique that can block sensory afferents from the skin and muscle wall of the abdomen. Local anaesthetic spreads posteriorly and cranio-caudally providing anaesthesia of the lateral and anterior intercostal nerves; 7 these lateral branches would be missed by rectus sheath block.…”
Section: Discussionmentioning
confidence: 99%
“…The use of remifentanil for cesarean section under general anesthesia has been reported in various clinical situations [7,[11][12][13][14][15], including those related to cardiac disease [7,[11][12][13], liver disease [14], and neurologic disease [15]. Most of these reports noted that the maternal hemodynamic changes associated with laryngoscopy and surgical incision could be managed with remifentanil without prolonged neonatal depression.…”
Section: Discussionmentioning
confidence: 97%